A STUDY ON THE PLIGHT OF MUSLIM WOMEN OF SALMAN RUSHDIE’S MIDNIGHT’S CHILDREN - V. , Suguna; K., Kokila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Islam is a highly orthodoxical religion and culture which considers woman as an inferior and subjugated being to man. The position of woman in it is considerably low. Marriage as a social institution does not confer any rights or power to women. Indeed, the married man is given freedom to have many wives and concubines. Women did not have any rights in the family as well as in the society during the pre-Prophet era. It was the Prophet who gave status and recognition to women in the Islamic culture. Even then, she cannot have control over her husband to have many wives. Divorcing a wife happens according to the whims and fancies of the husband. This research paper titled ‘A Study on the Plight of Muslim Women of Salman Rushdie’s Midnight’s Children’ throws light on the sufferings, distress, pain and agony of female Muslim characters of the novel.